Ursodeoxycholic acid : a molecular modulator of the inflammation-carcinoma sequence in the oesophagus? - Prichard, David (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Clinical Medicine, 2012)
Gastro-oesophageal reflux disease (GORD) is a prevalent disease, affecting up to 20% of the western population. In up to 10% of these patients Barrett’s Oesophagus (BO) will exist. This nietaplastic epithelium carries a risk of developing into oesophageal adenocarcinoma (OAC). BO and OAC have a negligible hereditary component; they are environmental diseases with GORD representing the most significant risk factor for both. The refluxate of GORD is predominantly comprised of acid and bile acids (BAs). The acid component of GORD has been successftilly targeted pharmacologically. Despite this, the incidence of BO and OAC has risen steadily over the last three decades. BAs remain the untreated component. Research has shown that BAs are pro- inflammatory, pro-apoptotic and carcinogenic molecules. Increasing exposure of the oesophagus to BAs correlates with an increasing risk of erosive oesophagitis, BO and OAC. Epidemiological studies have confirmed BAs as carcinogens in the oesophagus. Thus, there is a need for a safe and effective therapeutic which targets BA-induced toxicity in the oesophagus.
Keywords: Clinical Medicine, Ph.D.; Ph.D. Trinity College Dublin